2021
DOI: 10.1029/2020jd034341
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Convective Transport Over the Tropical Western Pacific From Trajectory Analyses

Abstract: This study characterizes the representation of convective transport by a Lagrangian trajectory model driven by kinematic (pressure tendency ω) vertical velocity. Four (re)analysis wind products are used in backward trajectory calculations with the TRAJ3D model, and their representations of convective transport are analyzed. Two observation‐based diagnostics are used for the evaluation: a database of observed convective cloud tops derived from satellite measurements and a set of transit time distributions (TTDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…There are two significant refinements in this approach over the previous study (Honomichl & Pan, 2020). First, the high spatial and temporal resolution of the ERA5 reanalysis winds improve the trajectory model representation of convective transport over the ERA-interim data (0.7° and 6 hourly, Dee et al, 2011) used in the earlier study, as demonstrated by Smith et al (2021). This improved representation is likely a key factor revealing the association of the primary region from which the air mass left the BL with the monsoon trough, the region known for deep convection and heavy rainfall (e.g., Krishnamurti & Bhalme, 1976).…”
Section: Eastward Eddy Sheddingmentioning
confidence: 91%
See 1 more Smart Citation
“…There are two significant refinements in this approach over the previous study (Honomichl & Pan, 2020). First, the high spatial and temporal resolution of the ERA5 reanalysis winds improve the trajectory model representation of convective transport over the ERA-interim data (0.7° and 6 hourly, Dee et al, 2011) used in the earlier study, as demonstrated by Smith et al (2021). This improved representation is likely a key factor revealing the association of the primary region from which the air mass left the BL with the monsoon trough, the region known for deep convection and heavy rainfall (e.g., Krishnamurti & Bhalme, 1976).…”
Section: Eastward Eddy Sheddingmentioning
confidence: 91%
“…This new result, largely owing to the much-improved representation of convective transport by using the ERA5 wind fields (Smith et al, 2021), brings clarity to results of previous studies of monsoon transport, in which the region of the southern flank of the Tibetan Plateau was shown to be the main vertical transport channel (e.g., Bergman et al, 2013;Honomichl & Pan, 2020;Pan et al, 2016). This result also provides the context for previous air mass origin studies that used tagged tracers or convective clouds which were identified using geographical regions or political boundaries (e.g., Bucci et al, 2020;Park et al, 2009;Vogel et al, 2015).…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…With respect to the importance of convection, Wu et al (2020) showed with a free-running CCM that for the first uplift in the ASM region convection is dominant but in the UTLS the large scale dynamics are most relevant for the tracer budget. A recent study by Smith et al (2021) investigated how convective processes are captured in the vertical velocity field of (re)analysis data. They came to the conclusion that kinematic trajectories based on (re)analyses winds incorporate the effects of convection to a substantial degree.…”
Section: Uncertainties In the Presented Resultsmentioning
confidence: 99%
“…The stratospheric intrusion is known to be dominated by isentropic mixing near the tropopause (Holton et al., 1995), which occurs at a finer spatial and temporal resolution compared to the given daily vertical velocity. As the pure trajectory model does not incorporate parameterization for convection, mixing, and turbulence, vertical displacement should be considered with potential uncertainties (W. P. Smith et al., 2021).…”
Section: Methodsmentioning
confidence: 99%